Generational Mean Analysis of Salt Tolerance during Osmotic Phase in Maize Seedling - Collado, Mónica B. (2019)
This study details the nature and magnitude of the genetic effects associated with various quantitative characters (morphological and hydric relations) measured in maize seedlings during the osmotic phase of saline stress (100 mM NaCl). Three lines with differential behavior in salt stress: SC2 (tolerant), AFE (susceptible) and LP3 (moderately tolerant) were used to obtain contrasting crosses (SC2 × AFE) and (SC2 × LP3). An analysis of six generational means (P 1, P 2, F 1, F 2, BC1 and B C 2) was applied for each cross. First a scaling test was applied and then a three and six-parameter genetic models were used to estimate various genetic components. In none of the traits studied there was evidence of adequacy to the three parameter model, which indicates important epistatic effects in genetic expression. The dominant genetic effects were greater than the additive ones for all the characters evaluated. LG showed positive and significant differences for [h] in both crosses, indicating the presence of hybrid vigor and its possible use in the improvement. Low value of [d] and high of [h] both significant in SC2 × AFE, indicates existence of genes dispersion between the parental lines. While, for the cross SC2 × LP3, the low and significant value of [d] and not significant value of [h], indicate greater genetic similarity. In the SC2 × LP3 cross, the negative interaction [l ] confirms ambidirectional dominance, while for SC2 × LP3 the positive sign indicates directional dominance. The analysis of tolerance to salinity in the osmotic phase showed a complex polygenic inheritance for the traits used, determined by simple and interaction effects of different magnitudes and significance according to the cross considered.